An interpretation attempt of Hungarian small towns’ shrinking in a post-socialist transformation context - András Trócsányi; Gábor Pirisi; Éva Máté (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The rapid shrinking of Hungarian small towns became such a general process after the turn of the Millennium, which does not simply reflect the overall effects of the second demographic transition, and could not even be interpreted with local and regional factors. The aim of the present paper is to analyse the shrinking of small towns among the framework of post-socialists urban trans-formation models and concepts. Many authors have dealt with such transformation issues, but rather focusing on the description of the development of larger cities and analysing the transformation of urban space and society. Despite the evident differences caused by the size of the researched settlements (small urban centres with a maximal population of 30,000 people), some general elements of these concepts give parts of the explanations we looked for. Others are rooted much deeper: our paper finally states that the present day crisis of small towns originates back to the later decades of planned economy, when the forced and somewhat over-dimensioned modernisation of small towns resulted a significant role in the urban network. This modernisation was centrally planned, led and financed, and with the exhaustion of these exogenous sources small towns seem to return to a less intensive development path.